PENGARUH LATIHAN BOW JUMPS TERHADAP DAYA LEDAK (EXPLOSIVE POWER) OTOT TUNGKAI PADA TIM BOLA VOLI MUSTANK PEKANBARU - Anggi Jummaida; Drs. Ramadi,S.Pd, M.Kes, AIFO '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was conducted to determine whether there is influence Bow exercise Jumps to the leg muscle explosive power in Pekanbaru Mustank volleyball team, so that when a jump smash to get the maximum leap. Forms of this research is the experimental treatment (Experimental), with a population of volleyball players Mustank Pekanbaru, the data in this study is the entire population of 10 people. The instruments used in this research is to test Vertical Jump, which aims to measure the explosive power leg muscle. After that, the data is processed with statistical, normality test with lilifors test at significance level α (0.05). The hypothesis is the influence of exercise Bow Jumps to the explosive power leg muscle. Based on t test analysis produces Ttabel Thitung of 0.2 and 0.258, meaning Thitung> Ttabel. Based on the analysis of statistical data, there are an average Pree-test of 40 and an average post-test 42.8, then the data is normal. Thus, there Effect of Exercise Bow Jumps on Explosive power on a Limb Muscle Volleyball Team Mustank Pekanbaru.Keywords : Bow Jumps, The Explosive Power Of Leg Muscle.